The methodological quality of diagnostic test accuracy studies for musculoskeletal conditions can be improved - Henschke, Nicholas; Keuerleber, Julia; Ferreira, Manuela; Maher, Christopher G.; Verhagen, Arianne P. (Journal of clinical epidemiology, 2014)
To provide an overview of reporting and methodological quality in diagnostic test accuracy (DTA) studies in the musculoskeletal field and evaluate the use of the QUality Assessment of Diagnostic Accuracy Studies (QUADAS) checklist.